Does aquascape have the ability to provide therapy? / Farhan Faat … [et al.] - Faat, Farhan; Elden, Sperico Michael; Badiuzaman, Ahmad Fauzan; Farhan, Mohamad; Nik Mohd Nor, Nik Mohd Shahril (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2023)
Even though aquariums are well-known and have physiological benefits, the term aquascape in aquarium appears to be unfamiliar to Malaysians. Aquascape has recently gained popularity as a hobby in Malaysia. This activity, also known as underwater gardening, entails creating a landscaped area with a conspicuous natural or constructed aquatic feature, and artfully arranging aquatic plants, as well as rocks, stones, cave work, or driftwood, in an aquarium in an aesthetically pleasing manner. It is well known that some people visit a fish shop to relax, and aquascape therapy may be able to reduce tension. This study empirically investigates the perspective of aquascape on the therapeutic effect of aquarium viewing. This study empirically examines the perspective of 114 customers regarding aquascape as the therapeutic effect of observing aquariums. The respondent's insightful perspective on the investigation issue could make a positive contribution.